Rab5-mediated VE-cadherin internalization regulates the barrier function of the lung microvascular endothelium - Yang, Junjun (Cell Mol Life Sci, 2015)
The small GTPase Rab5 has been well defined to control the vesicle-mediated plasma membrane protein transport to the endosomal compartment. However, its function in the internalization of vascular endothelial (VE)-cadherin, an important component of adherens junctions, and as a result regulating the endothelial cell polarity and barrier function remain unknown. Here, we demonstrated that lipopolysaccharide (LPS) simulation markedly enhanced the activation and expression of Rab5 in human pulmonary microvascular endothelial cells (HPMECs), which is accompanied by VE-cadherin internalization. In parallel, LPS challenge also induced abnormal cell polarity and dysfunction of the endothelial barrier in HPMECs. LPS stimulation promoted the translocation of VE-cadherin from the plasma membrane to intracellular compartments, and intracellularly expressed VE-cadherin was extensively colocalized with Rab5. Small interfering RNA (siRNA)-mediated depletion of Rab5a expression attenuated the disruption of LPS-induced internalization of VE-cadherin and the disorder of cell polarity. Furthermore, knockdown of Rab5 inhibited the vascular endothelial hyperpermeability and protected endothelial barrier function from LPS injury, both in vitro and in vivo. These results suggest that Rab5 is a critical mediator of LPS-induced endothelial barrier dysfunction, which is likely mediated through regulating VE-cadherin internalization. These findings provide evidence, implicating that Rab5a is a potential therapeutic target for preventing endothelial barrier disruption and vascular inflammation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00018-015-1973-4) contains supplementary material, which is available to authorized users.